2021
DOI: 10.32481/djph.2021.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Alzheimer’s Disease:

Abstract: Finding earlier and more definitive ways to diagnose AD has been the subject of significant amounts of research, and testing advances have been seen in the last decade with expanded use of positron emission tomography (PET) and magnetic resonance imaging (MRI), as well as in the identification of biomarkers in cerebrospinal fluid (CSF) and more recently serum. While limited, some of these diagnostic advances are available to the public, though typically at a high price.A high-level overview of emerging diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 116 publications
0
11
0
Order By: Relevance
“…APOE ε4 allele, usually existing in approximately 15% of people, lowers the age of AD onset and increases the risk of AD in a dose-dependent manner (Levy et al, 1990 ; Wallon et al, 2012 ; Ward et al, 2012 ; Tang et al, 2016 ). Accumulating difficulties remain when Aβ-targeting interference fails to effectively halt or slow clinical AD progression (Bohrmann et al, 2012 ; Salloway et al, 2014 ; Bomasang-Layno and Bronsther, 2021 ; Pleen and Townley, 2022 ); thus, it is widely believed that amyloid cascading seems to appear as less possibility for a major explanation of AD pathogenesis. Other rising insights draw more and more interests broadly.…”
Section: Introductionmentioning
confidence: 99%
“…APOE ε4 allele, usually existing in approximately 15% of people, lowers the age of AD onset and increases the risk of AD in a dose-dependent manner (Levy et al, 1990 ; Wallon et al, 2012 ; Ward et al, 2012 ; Tang et al, 2016 ). Accumulating difficulties remain when Aβ-targeting interference fails to effectively halt or slow clinical AD progression (Bohrmann et al, 2012 ; Salloway et al, 2014 ; Bomasang-Layno and Bronsther, 2021 ; Pleen and Townley, 2022 ); thus, it is widely believed that amyloid cascading seems to appear as less possibility for a major explanation of AD pathogenesis. Other rising insights draw more and more interests broadly.…”
Section: Introductionmentioning
confidence: 99%
“…5 ). This trend might be related to the treatment guidelines for AD 25 , 26 as well as the reimbursement criteria of the Korean National Health Insurance 24 . Previous meta-analyses have revealed that AChEIs delay cognitive dysfunction and decline in performance of daily activities for 6–12 months on average and slow the decline in global clinical dementia rating 27 , 28 ; therefore, they are recommended for use from the initial stages of AD 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Type III hyperlipoproteinemia, also called familial hypercholesterolemia, is a rare type of mixed hyperlipidemia in which cholesterol and triglyceride levels are above the normal value [2,7]. The disease may be associated with mutations in two places of the APOE gene, which are inherited in an autosomal recessive manner and lead to impaired fat metabolism [19].…”
Section: Type III Hyperlipoproteinemiamentioning
confidence: 99%
“…It is most often diagnosed in people over the age of 65, but also in younger individuals [1]. Characteristic symptoms of the disease include memory loss, difficulties in everyday activities, disorientation, problems with concentration and spatial orientation, and many other disorders related to the improper functioning of the brain [2]. According to the Institute for Health Metrics and Evaluations (IHME), in Poland in 2019, the estimated percentage of people suffering from Alzheimer's disease and related diseases was 1.5% (585,000 people), which was 0.2 percent higher than in 2014.…”
Section: Introductionmentioning
confidence: 99%